A Workshop for Addressing the Impact of the Imposter Syndrome on Clinical Nurse Specialists. Issue 4 (July 2018) - Haney, Tina Sweeney; Birkholz, Lorri; Rutledge, Carolyn
Abstract : Purpose: The imposter syndrome creates feelings of self-doubt in individuals, which can result in emotional paralysis preventing them from achieving their fullest potential. Clinical nurse specialists are not immune to this phenomenon. The purpose of this article is to describe an educational program designed to assist healthcare professionals, including clinical nurse specialist students, in identifying, understanding, and addressing imposter syndrome. Description of Program: Interprofessional students from 8 professions came together for a 2-week interprofessional education experience that included a 1-day workshop. After experiential team building and small group encounters with complicated standardized patients, students were introduced to the imposter syndrome. Students completed the Clance Impostor Phenomenon Scale and engaged in rich dialogue about the phenomenon, its effects, and personal strategies to overcome its impact. Outcome: When surveyed using the Clance Impostor Phenomenon Scale, clinical nurse specialist students consistently had high imposter tendencies. As a result of the program, students expressed feelings of liberation and empowerment. Conclusion: Clinical nurse specialist students can be impacted by the imposter syndrome, which has a potential to decrease their confidence, thus limiting their ability to practice at their highest potential. Programs that empower the clinical nurse specialists to recognize and address this phenomenon may increase their ability to optimize their role in healthcare.